Sung birds : music, nature, and poetry in the later Middle Ages - Leach, Elizabeth Eva (Cornell University Press, 2007)
"Is birdsong music? The most frequent answer to this question in the Middle Ages was resoundingly no. In Sung Birds, Elizabeth Eva Leach traces postmedieval uses of birdsong within Western musical culture. She first explains why such melodious sound was not music for medieval thinkers and then goes on to consider the ontology of music, the significance of comparisons between singers and birds, and the relationship between art and nature as enacted by the musical performance of late-medieval poetry."--Jacket